Alkali-resistant nanofiltration membrane capable of separating cellulose substances from calcium and magnesium ions and preparation method thereof
Patent Information
- Application Number
- CN202611467936.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
现有纳滤膜在此类强碱环境中长期运行时,膜材料易发生降解,同时纤维素等大分子易堵塞膜孔,导致膜需频繁清洗甚至更换,严重影响运行效率和使用寿命
[0025]本发明利用亲水性聚乙二醇材料改善聚砜类树脂的疏水性;通过掺杂耐碱无机纳米颗粒,从本质上提升纳滤膜基底的耐碱性,并优化基底膜海绵状孔与指状孔结构以及孔隙率与孔径之间的不平衡。
Smart Images

Figure CN122974154A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer functional membrane materials and their preparation technology, specifically relating to an alkali-resistant nanofiltration membrane capable of separating cellulose substances from calcium and magnesium ions and its preparation method. Background Technology
[0002] Nanofiltration membranes, as a highly efficient separation technology, play an important role in wastewater treatment and resource recovery in industries such as chemical, textile, food, and pharmaceutical. Nanofiltration membranes can typically retain substances with molecular weights between 200 and 2000 Da, and through mechanisms such as pore size sieving, Donnan equilibrium, and dielectric effect, they can achieve selective separation of ions of different valence states, organic pollutants, and active drug molecules.
[0003] Currently, domestically produced nanofiltration membranes can achieve basic separation of monovalent and divalent ions, but the retention rate of divalent ions such as calcium and magnesium still needs to be improved. In addition, the application of nanofiltration membranes in complex industrial environments also faces problems such as insufficient acid and alkali resistance, the trade-off between membrane flux and retention rate, membrane fouling, and scaling.
[0004] Wastewater from the alkaline leaching process of chemical fibers in the textile industry contains high concentrations of alkaline solutions, cellulose, and hemicellulose. When existing nanofiltration membranes operate in such highly alkaline environments for extended periods, the membrane material is prone to degradation, and large molecules such as cellulose easily clog the membrane pores, leading to frequent cleaning and even replacement, severely impacting operating efficiency and lifespan. Similarly, in applications such as seawater desalination, nanofiltration membranes face the challenge of balancing high rejection rates and high flux, as well as the susceptibility of membrane surface fouling.
[0005] Therefore, there is an urgent need to develop a nanofiltration membrane that combines alkali resistance and good separation performance to achieve efficient retention of cellulose and calcium and magnesium ions under strong alkaline load conditions, while maintaining a reasonable membrane flux. Summary of the Invention
[0006] To address the aforementioned technical problems, this invention provides an alkali-resistant nanofiltration membrane capable of separating cellulose-based substances from calcium and magnesium ions, and a method for preparing the same.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] An alkali-resistant nanofiltration membrane capable of separating cellulose-based substances from calcium and magnesium ions, the alkali-resistant nanofiltration membrane comprising a base membrane and a surface separation functional layer covering the base membrane;
[0009] The surface separation functional layer is a polymer elastomer-modified polyamide layer; the polymer elastomer-modified polyamide layer is prepared by an interfacial polymerization reaction between an aqueous solution and an oil solution on the surface of a base film.
[0010] The aqueous solution contains amine monomers, and the oil solution contains acyl chloride monomers and polymer elastomers.
[0011] A further improvement of the technical solution of the present invention is that the base film is prepared by phase inversion of polysulfone resin, polymer elastomer, polyethylene glycol and inorganic nanoparticles uniformly dispersed in a solvent.
[0012] A further improvement of the technical solution of the present invention is that the polysulfone resin is one of polysulfone and polyethersulfone; the polymer elastomer is at least one of poly(acrylonitrile-co-butadiene), polychloroprene, and polyvinylidene fluoride; the inorganic nanoparticles are at least one of lithium chloride nanoparticles, zirconium dioxide nanoparticles, and magnesium oxide nanoparticles; and the solvent is at least one of N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone.
[0013] A further improvement of the technical solution of the present invention is that the amine monomer includes piperazine and a second amine monomer, wherein the second amine monomer is at least one of m-phenylenediamine, diethylenetriamine and triethylenetetramine; and the acyl chloride monomer is at least one of pyromellitic trimethylol chloride, terephthalic acid dimethylol chloride and isophthalic acid dimethylol chloride.
[0014] This invention also discloses a method for preparing the alkali-resistant nanofiltration membrane capable of separating cellulose substances and calcium and magnesium ions, comprising the following steps:
[0015] S1. Add polysulfone resin and polymer elastomer to a solvent. After the polysulfone resin and polymer elastomer have dissolved, add polyethylene glycol and inorganic nanoparticles to the system in sequence and stir continuously at room temperature for 12-24 hours. Then, reduce the stirring speed to degas the mixture and continue stirring for 12-24 hours to obtain a uniform casting solution.
[0016] S2. The casting solution prepared in step S1 is coated and then immersed in water for phase inversion to obtain the base film;
[0017] S3. The substrate membrane prepared in step S2 is immersed in an aqueous solution containing amine monomers. After immersion, the membrane is removed and excess solution on its surface is removed. Then, it is immersed in an oil solution containing acyl chloride monomers and polymer elastomers to carry out interfacial polymerization reaction and deposit a surface separation functional layer. Finally, the nanofiltration membrane with the surface separation functional layer is heat-treated to obtain the alkali-resistant nanofiltration membrane.
[0018] Further, in step S1, the mass ratio of the polymer elastomer to the polysulfone resin is (0.1~0.3):1; the mass ratio of the solvent to the polysulfone resin is (3~6):1; the mass ratio of the polyethylene glycol to the polysulfone resin is (0.05~0.2):1; and the mass ratio of the inorganic nanoparticles to the polysulfone resin is (0.2~1):1.
[0019] Furthermore, in step S2, the phase transformation temperature is 15~40℃ and the phase transformation time is 0.5~2.0min.
[0020] Further, in step S3, the content of piperazine in the aqueous solution containing amine monomers is 0.02 g / mL, and the total content of the second amine monomers is 0.01~0.03 g / mL, based on the total volume of the aqueous solution; the soaking time is 1~5 min.
[0021] In the oil phase solution containing acyl chloride monomer and polymer elastomer, based on the total volume of the oil phase solution, the content of acyl chloride monomer is 3.0 mg / mL, and the content of polymer elastomer is 0.5~2.0 mg / mL; the solvent of the oil phase solution is n-hexane and dichloromethane, and the volume ratio of n-hexane to dichloromethane is (35~45):1; the interfacial polymerization reaction time is 10~120 s.
[0022] Furthermore, in step S3, the heat treatment temperature is 50~80℃ and the time is 1~10min.
[0023] Furthermore, the step also includes step S4, which involves immersing the alkali-resistant nanofiltration membrane prepared in step S3 in a mixed solution of deionized water and ethanol for preservation.
[0024] Due to the adoption of the above technical solution, the beneficial effects of the present invention are as follows:
[0025] This invention utilizes hydrophilic polyethylene glycol materials to improve the hydrophobicity of polysulfone resins; by doping with alkali-resistant inorganic nanoparticles, it fundamentally enhances the alkali resistance of the nanofiltration membrane substrate and optimizes the sponge-like and finger-like pore structures of the substrate membrane as well as the imbalance between porosity and pore size.
[0026] This invention utilizes flexible polymer elastomer materials containing polar functional groups such as fluorine, chlorine, or cyano groups, allowing them to interpenetrate in situ between a rigid nanofiltration membrane substrate and a surface separation functional layer, thereby achieving synergistic optimization of membrane structure and performance.
[0027] On the one hand, because flexible polymer elastomer segments can be embedded in the microporous framework of rigid substrates, they form an interpenetrating network structure through physical entanglement between molecular chains and interfacial interaction with the substrate material, effectively improving the mechanical strength and pore structure support stability of nanofiltration membranes, inhibiting pore deformation and collapse, thereby reducing the risk of irreversible blockage caused by easy deformation of membrane pores and extending the service life of membranes.
[0028] Secondly, polar functional groups such as fluorine, chlorine, or cyano groups can construct "physical cross-linking" structures between polymer segments through dipole-dipole interactions and intermolecular forces such as hydrogen bonds. This physical cross-linking structure not only enhances the cohesive strength of the polymer network but also allows for in-situ fine-tuning and regularization of the pore structure of the substrate, optimizing pore size distribution and connectivity, thus providing a structural basis for achieving both high throughput and high retention. Thirdly, polar functional groups can participate in and regulate the monomer diffusion and reaction kinetics during the interfacial polymerization process. Through polar interactions, they can influence the contact and reaction rate of amine monomers and acyl chloride monomers at the oil-water interface, thereby adjusting the degree of crosslinking and microstructure of the surface separation functional layer and significantly alleviating the traditional "one-to-one" constraint between retention rate and membrane flux.
[0029] This invention achieves a synergistic improvement in membrane pore structure, surface separation layer morphology, and separation performance through in-situ interpenetration of flexible polymer elastomer materials and multiple regulation effects of polar functional groups. It effectively breaks through the bottleneck of mutual restriction between rejection rate and membrane flux in traditional nanofiltration membranes and has significant application value in the development of high-performance nanofiltration membranes. Attached Figure Description
[0030] Figure 1 This is a scanning electron microscope image of the product of Embodiment 1 of the present invention. Detailed Implementation
[0031] The present invention will be further described below with reference to embodiments. It should be understood that the preferred embodiments described herein are for illustrative and understanding purposes only and are not intended to limit the scope of the invention.
[0032] Unless otherwise specified, all raw materials used in the embodiments of the present invention are commercially available, all equipment used are conventional equipment in this technical field, and all methods used are conventional methods in this technical field.
[0033] Example 1
[0034] A method for preparing a poly(acrylonitrile-co-butadiene) blended polyethersulfone nanofiltration membrane includes the following steps:
[0035] S1. Preparation of polyethersulfone-poly(acrylonitrile-co-butadiene)-lithium chloride casting solution
[0036] Weigh 15.0 g of polyethersulfone and 2.25 g of poly(acrylonitrile-co-butadiene) and place them in a reaction vessel. Add 50.0 mL of N,N-dimethylacetamide and stir at 300 r / min to dissolve. After the polymer is completely dissolved, add 1.35 mL of polyethylene glycol and 7.5 g of lithium chloride nanoparticles to the system in sequence. Stir continuously at 300 r / min at 25 °C for 12 h to ensure that the components are fully mixed. Then, reduce the speed to 50 r / min for degassing treatment and continue stirring for 12 h. Finally, a uniform casting solution is obtained.
[0037] S2. Preparation of polyethersulfone-poly(acrylonitrile-co-butadiene)-lithium chloride substrate film
[0038] The casting solution prepared in step S1 was poured into an automatic coating machine, and the thickness was adjusted to 200 μm for coating. Then, the coated casting solution was immersed in water and phase inversion was carried out at 25°C for 1.2 min. The resulting base film was washed three times with deionized water to completely replace the solvent in the base film.
[0039] S3. Preparation of polyethersulfone-poly(acrylonitrile-co-butadiene)-lithium chloride nanofiltration membrane
[0040] First, the substrate membrane prepared in step S2 was immersed in an aqueous solution containing 0.02 g / mL piperazine and 0.02 g / mL diethylenetriamine for 5 min at 25 °C. Then, it was removed and the solution on the membrane surface was dried. Next, the membrane was placed in an oil phase solution containing 2.0 mg / mL poly(acrylonitrile-co-butadiene) and 3.0 mg / mL trimesoyl chloride (the solvent of the oil phase solution is a mixed solvent composed of dichloromethane and n-hexane in a volume ratio of 1:40) for 30 s to carry out an interfacial polymerization reaction to deposit a surface separation functional layer. The membrane surface was then rinsed three times with n-hexane to remove excess reactants. Finally, the complete nanofiltration membrane with the surface separation functional layer was placed in a 60 °C oven for 10 min to allow the trimesoyl chloride and piperazine-diethylenetriamine to react completely, resulting in a poly(acrylonitrile-co-butadiene) blended polyethersulfone nanofiltration membrane with cyano polar groups.
[0041] S4. Nanofiltration Membrane Post-processing and Storage
[0042] The nanofiltration membrane prepared in step S3 was immersed in a mixed solution of deionized water and anhydrous ethanol at a volume ratio of 4:1 and stored at 25°C.
[0043] Example 2
[0044] A method for preparing a polychloroprene blended polyethersulfone nanofiltration membrane includes the following steps:
[0045] S1. Preparation of polyethersulfone-polychloroprene-zirconia casting solution
[0046] Weigh 15.0 g of polyethersulfone and 1.5 g of polychloroprene, place them in a reaction vessel, add 45.0 mL of N-methylpyrrolidone, and stir at 300 r / min to dissolve. After the polymer is completely dissolved, add 0.75 mL of polyethylene glycol and 3.0 g of zirconium dioxide nanoparticles to the system sequentially, and stir continuously at 25 °C and 300 r / min for 24 h to ensure thorough mixing of all components. Subsequently, reduce the stirring speed to 50 r / min for degassing treatment and continue stirring for 24 h. Finally, a uniform casting solution is obtained.
[0047] S2. Preparation of polyethersulfone-polychloroprene-zirconia substrate film
[0048] The casting solution prepared in step S1 was poured into an automatic coating machine, and the thickness was adjusted to 200 μm for coating. Then, the smoothed casting solution was immersed in water and phase inversion was carried out at 15°C for 2.0 min. The resulting base film was washed with deionized water three times to completely replace the solvent in the base film.
[0049] S3. Preparation of polyethersulfone-polychloroprene-zirconia nanofiltration membrane
[0050] First, the substrate membrane prepared in step S2 was immersed in an aqueous solution containing 0.02 g / mL piperazine, 0.02 g / mL triethylenetetramine, and 0.01 g / mL diethylenetriamine for 1 min at 25 °C. Afterward, the membrane was removed and the solution on the membrane surface was dried. Then, the membrane was placed in an oil phase solution containing 0.5 mg / mL polychloroprene and 3.0 mg / mL isophthaloyl chloride (the solvent of the oil phase solution was a mixture of dichloromethane and n-hexane in a volume ratio of 1:35) for 120 s to perform an interfacial polymerization reaction, depositing a surface separation functional layer. The membrane surface was then rinsed three times with n-hexane to remove excess reactants. Finally, the complete nanofiltration membrane with the surface separation functional layer was placed in a 50 °C oven for 8 min to ensure complete reaction between isophthaloyl chloride and piperazine-diethylenetriamine-triethylenetetramine; thus obtaining a polychloroprene blended polyethersulfone nanofiltration membrane with polar chlorinated derivatives.
[0051] S4. Nanofiltration Membrane Post-processing and Storage
[0052] Same as step S4 in Example 1.
[0053] Example 3
[0054] A method for preparing a polyvinylidene fluoride blended polysulfone nanofiltration membrane includes the following steps:
[0055] S1. Preparation of polysulfone-polyvinylidene fluoride-magnesium oxide casting solution
[0056] Weigh 15.0 g of polysulfone and 4.5 g of polyvinylidene fluoride and place them in a reaction vessel. Add 90.0 mL of a mixed solvent consisting of N,N-dimethylacetamide and dimethyl sulfoxide in a volume ratio of 1:1. Stir at 300 r / min to dissolve the polymer. After the polymer is completely dissolved, add 2.6 mL of polyethylene glycol and 15.0 g of magnesium oxide nanoparticles to the system sequentially. Stir continuously at 300 r / min at 25 °C for 18 h to ensure thorough mixing of all components. Then, reduce the stirring speed to 50 r / min for degassing and continue stirring for 18 h. Finally, a uniform casting solution is obtained.
[0057] S2. Preparation of polysulfone-polyvinylidene fluoride-magnesium oxide substrate film
[0058] The casting solution prepared in step S1 was poured into an automatic coating machine, and the thickness was adjusted to 200 μm for coating. Then, the smoothed casting solution was immersed in water and phase-inverted at 40°C to form a film for 30 seconds. The resulting base film was washed three times with deionized water to completely replace the solvent in the base film.
[0059] S3. Preparation of polysulfone-polyvinylidene fluoride-magnesium oxide nanofiltration membrane
[0060] First, the substrate membrane prepared in step S2 was immersed in an aqueous solution of 0.02 g / mL piperazine and 0.01 g / mL m-phenylenediamine for 3 min at 25 °C. Then, it was removed and the solution on the membrane surface was dried. Next, the membrane was placed in an oil phase solution containing 1.2 mg / mL polyvinylidene fluoride and 3.0 mg / mL terephthaloyl chloride (the solvent of the oil phase solution is a mixed solvent composed of dichloromethane and n-hexane in a volume ratio of 1:45) for 10 s to carry out an interfacial polymerization reaction, depositing a surface separation functional layer. The membrane surface was then rinsed three times with n-hexane to remove excess reactants. Finally, the complete nanofiltration membrane with the surface separation functional layer was placed in an 80 °C oven for 5 min to allow the terephthaloyl chloride and piperazine-m-phenylenediamine to react completely, resulting in a polyvinylidene fluoride blended polysulfone nanofiltration membrane with polar fluorinated derivatives.
[0061] (4) Post-processing and preservation of nanofiltration membranes
[0062] Same as step S4 in Example 1.
[0063] The polymer elastomer is selected from at least one of poly(acrylonitrile-co-butadiene), polychloroprene, and polyvinylidene fluoride; the inorganic nanoparticles are selected from at least one of lithium chloride nanoparticles, zirconium dioxide nanoparticles, and magnesium oxide nanoparticles; the solvent is selected from at least one of N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone; and the acyl chloride monomer is selected from at least one of trimesoyl chloride, terephthaloyl chloride, and isophthaloyl chloride. In this invention, the selection of the polymer elastomer, inorganic nanoparticles, solvent, and acyl chloride monomer is independent of each other; the polymer elastomer can be used alone, or in combination of two or three; the inorganic nanoparticles can be any one of the nanoparticles, or in combination of two, three, or four; the solvent can be any one of the solvents, or in combination of two or three; and the acyl chloride monomer can be any one of the acyl chloride monomers, or in combination of two or three. For example, poly(acrylonitrile-co-butadiene) can be used as the polymer elastomer, combined with zirconium dioxide nanoparticles and N,N-dimethylacetamide solvent, with pyromellitic trimethylol chloride as the acyl chloride monomer; alternatively, polyvinylidene fluoride can be used as the polymer elastomer, combined with a mixture of lithium chloride nanoparticles and magnesium oxide nanoparticles, using a mixture of N-methylpyrrolidone and dimethyl sulfoxide solvent, and a mixture of terephthalic acid chloride and isophthalic acid chloride monomers.
[0064] Comparative Example 1
[0065] A method for preparing a polyethersulfone nanofiltration membrane, differing from Example 1 in that the base membrane and surface separation functional layer do not contain the polymer elastomer poly(acrylonitrile-co-butadiene); includes the following steps:
[0066] S1. Preparation of polyethersulfone-lithium chloride casting solution
[0067] Weigh 15.0 g of polyethersulfone and place it in a reaction vessel. Add 50.0 mL of N,N-dimethylacetamide and stir at 300 r / min to dissolve. After the polyethersulfone is completely dissolved, add 1.35 mL of polyethylene glycol and 7.5 g of lithium chloride nanoparticles to the system in sequence. Stir continuously at 300 r / min at 25 °C for 12 h to ensure that the components are fully mixed. Then, reduce the speed to 50 r / min for degassing treatment and continue stirring for 12 h. Finally, a uniform, transparent, and bubble-free casting solution is obtained.
[0068] S2. Preparation of polyethersulfone-lithium chloride substrate film
[0069] The casting solution prepared in step S1 was poured into an automatic coating machine, and the thickness was adjusted to 200 μm for coating. Then, the coated casting solution was immersed in water and phase inversion was carried out at 25°C for 1.2 min. The resulting base film was washed three times with deionized water to completely replace the solvent in the base film.
[0070] S3. Preparation of polyethersulfone-lithium chloride nanofiltration membrane
[0071] First, the substrate membrane prepared in step S2 was immersed in an aqueous solution containing 0.02 g / mL piperazine and 0.02 g / mL diethylenetriamine for 5 min at 25 °C. Then, it was removed and the solution on the membrane surface was dried. Next, the membrane was placed in an oil phase solution containing 3.0 mg / mL trimesoyl chloride (the oil phase solvent was n-hexane) for 30 s for interfacial polymerization to deposit a surface separation functional layer. The membrane surface was then rinsed three times with n-hexane to remove excess reactants. Finally, the complete nanofiltration membrane with the prepared surface separation functional layer was placed in a 60 °C oven for 10 min to ensure complete reaction between trimesoyl chloride and piperazine-diethylenetriamine. This yielded a polyethersulfone-lithium chloride nanofiltration membrane without interpenetration of elastomer materials.
[0072] S4. Nanofiltration Membrane Post-processing and Storage
[0073] Same as step S4 in Example 1.
[0074] Comparative Example 2
[0075] A method for preparing a polyethersulfone nanofiltration membrane, differing from Example 2 in that the base membrane and surface separation functional layer do not contain the polymer elastomer polychloroprene; the method includes the following steps:
[0076] S1. Preparation of polyethersulfone-zirconia casting solution
[0077] 15.0 g of polyethersulfone was weighed and placed in a reaction vessel. 45.0 mL of N-methylpyrrolidone was added, and the mixture was stirred at 300 rpm to dissolve. After the polymer was completely dissolved, 0.63 mL of polyethylene glycol and 3.0 g of zirconium dioxide nanoparticles were added sequentially to the system. The mixture was stirred continuously at 25 °C and 300 rpm for 24 h to ensure thorough mixing of all components. Subsequently, the stirring speed was reduced to 50 rpm for degassing, and stirring was continued for another 24 h. Finally, a uniform casting solution was obtained.
[0078] S2. Preparation of polyethersulfone-zirconia substrate film
[0079] The casting solution prepared in step S1 was poured into an automatic coating machine, and the thickness was adjusted to 200 μm for coating. Then, the smoothed casting solution was immersed in water and phase inversion was carried out at 15°C for 2.0 min. The resulting base film was washed with deionized water three times to completely replace the solvent in the base film.
[0080] S3. Preparation of polyethersulfone-zirconia nanofiltration membrane
[0081] First, the substrate membrane prepared in step S2 was immersed in an aqueous solution containing 0.02 g / mL piperazine, 0.02 g / mL triethylenetetramine, and 0.01 g / mL diethylenetriamine for 1 min at 25 °C. Then, the membrane was removed, and the solution on the membrane surface was dried. Next, the membrane was immersed in an oil-phase solution containing 3.0 mg / mL isophthaloyl chloride (hexane as the oil phase solvent) for 120 s to perform an interfacial polymerization reaction, depositing a surface separation functional layer. The membrane surface was then rinsed three times with hexane to remove excess reactants. Finally, the complete nanofiltration membrane with the surface separation functional layer was placed in a 50 °C oven for 8 min to ensure complete reaction between the isophthaloyl chloride and piperazine-triethylenetetramine, resulting in a polyethersulfone-zirconia nanofiltration membrane without elastomer interpenetration.
[0082] S4. Nanofiltration Membrane Post-processing and Storage
[0083] Same as step S4 in Example 1.
[0084] Comparative Example 3
[0085] A method for preparing a polyethersulfone nanofiltration membrane, differing from Example 3 in that the base membrane and surface separation functional layer do not contain the polymer elastomer polyvinylidene fluoride; the method includes the following steps:
[0086] S1. Preparation of polysulfone-magnesium oxide casting solution
[0087] Weigh 15.0 g of polysulfone and place it in a reaction vessel. Add 90.0 mL of a mixed solvent consisting of N,N-dimethylacetamide and dimethyl sulfoxide in a volume ratio of 1:1. Stir at 300 r / min to dissolve the polymer. After the polymer is completely dissolved, add 2.5 mL of polyethylene glycol and 15.0 g of magnesium oxide nanoparticles to the system in sequence. Stir continuously at 300 r / min at 25 °C for 18 h to ensure that the components are fully mixed. Then, reduce the speed to 50 r / min for degassing treatment and continue stirring for 18 h. Finally, a uniform casting solution is obtained.
[0088] S2. Preparation of polysulfone-magnesium oxide substrate film
[0089] The casting solution prepared in step S1 was poured into an automatic coating machine, and the thickness was adjusted to 200 μm for coating. Then, the smoothed casting solution was immersed in water and phase-inverted at 40°C to form a film for 30 seconds. The resulting base film was washed three times with deionized water to completely replace the solvent in the base film.
[0090] S3. Preparation of polysulfone-magnesium oxide nanofiltration membrane
[0091] First, the substrate membrane prepared in step S2 was immersed in an aqueous solution of 0.02 g / mL piperazine and 0.01 g / mL m-phenylenediamine for 3 min at 25 °C. Then, it was removed, and the membrane surface was dried. Next, the membrane was immersed in an oil-phase solution of 3.0 mg / mL terephthaloyl chloride (hexane as the oil phase solvent) for 10 s to perform interfacial polymerization, depositing a surface separation functional layer. The membrane surface was then rinsed three times with hexane to remove excess reactants. Finally, the complete nanofiltration membrane with the surface separation functional layer was placed in an 80 °C oven for 5 min to ensure complete reaction between terephthaloyl chloride and piperazine-m-phenylenediamine, resulting in a polyethersulfone-magnesium oxide nanofiltration membrane without elastomer interpenetration.
[0092] (4) Post-processing and preservation of nanofiltration membranes
[0093] Same as step S4 in Example 1.
[0094] Performance testing:
[0095] 1) Retention rate and membrane flux performance testing
[0096] Using a cross-flow filtration device, the calcium and magnesium ion rejection rates and membrane flux performance of the nanofiltration membranes prepared in Examples 1-3 and Comparative Examples 1-3 were tested. The nanofiltration membranes were cut into suitable circular pieces and fixed in the membrane module. The membranes were pre-pressed at 0.6 MPa for 30-60 min. After the effluent stabilized, the pressure was adjusted to 0.5 MPa, and testing continued. The concentrations of magnesium sulfate and calcium chloride aqueous solutions were 2000 ppm (standard); the black liquor mainly contained 85 g / L cellulose and 10 g / L sodium hydroxide. The test results are shown in Table 1.
[0097] Table 1
[0098] As shown in Table 1, compared with Comparative Example 1, the nanofiltration membrane prepared in Example 1 maintains a high membrane flux while exhibiting excellent retention performance, effectively overcoming the traditional trade-off between retention rate and membrane flux. This performance advantage mainly stems from the fact that the poly(acrylonitrile-co-butadiene) elastomer material interpenetrates in situ between the base membrane and the surface separation functional layer, allowing for the regulation of the pore structure. This improves retention performance while reducing the negative impact on membrane flux. Simultaneously, the hydrophilic cyano functional groups in its molecular structure can form weak hydrogen bonds and polar interactions with the aqueous interface, helping to uniformly regulate the interfacial polymerization rate and promote the formation of a denser and more uniform "Turing-ridge" network structure. This enhances the membrane's ability to retain organic matter and divalent ions, achieving synergistic optimization of retention rate and membrane flux, and alleviating the imbalance between the two.
[0099] Further comparison of Examples 2 and 3 with Comparative Examples 2 and 3 shows that the introduction of polymer elastomers containing hydrophobic functional groups such as fluorine or chlorine helps to improve membrane flux while having almost no impact on retention performance, breaking through the traditional "inverse relationship" between retention rate and membrane flux. This is mainly attributed to the following: on the one hand, the introduction of polymer elastomer materials can regulate the pore structure of nanofiltration membranes, giving them higher flux; on the other hand, although their hydrophobic and polar functional groups are somewhat unfavorable to the crosslinking of the surface separation functional layer, the interaction between polar molecules can form a "physical crosslinking structure," which optimizes and compensates for the morphology of the surface separation layer, thereby achieving a significant increase in membrane flux without significantly compromising the retention rate.
[0100] 2) Alkali resistance test of nanofiltration membrane
[0101] The nanofiltration membranes prepared in Example 1 and Comparative Example 1 were immersed in a 10 g / L sodium hydroxide solution at room temperature for 72 h. Subsequently, the black liquor cellulose rejection rate of the two nanofiltration membranes after alkali immersion was tested using a cross-flow filtration device and compared with the black liquor cellulose rejection rate before alkali immersion. The rejection rate recovery rate was calculated to evaluate the alkali resistance of the nanofiltration membranes. The results are shown in Table 2.
[0102] Table 2
[0103] As shown in Table 2, the retention recovery rate of Example 1 was 95.2%, which was higher than that of Comparative Example 1 (90.7%). The experimental results indicate that the nanofiltration membrane prepared in Example 1 has stronger alkali resistance.
[0104] 3) Scanning electron microscopy test
[0105] The alkali-resistant nanofiltration membrane prepared in Example 1 was subjected to scanning electron microscopy to observe its surface microstructure, such as... Figure 1As shown, the alkali-resistant nanofiltration membrane prepared in Example 1 has a uniform, dense, and complex "Turing and ridge" network structure, which is more conducive to the retention of calcium and magnesium ions and cellulose. This is attributed to the fact that the hydrophilic cyano functional groups in poly(acrylonitrile-co-butadiene) form weak hydrogen bonds and polar molecular forces with the aqueous phase interface, which can more uniformly regulate the interfacial reaction rate, increase the degree of crosslinking, and make the crosslinked network growth more uniform and dense, which is more conducive to the retention of substances.
[0106] The present invention has been described in detail with reference to the above embodiments. It should be noted that the above embodiments are merely illustrative examples. Without departing from the spirit and essence of the present invention, those skilled in the art can devise various alternatives and improvements to the present invention, all of which should be understood to be within the scope of protection of the present invention.
Claims
1. An alkali-resistant nanofiltration membrane capable of separating cellulose-based substances from calcium and magnesium ions, characterized in that, The alkali-resistant nanofiltration membrane includes a base membrane and a surface separation functional layer covering the base membrane; The surface separation functional layer is a polymer elastomer-modified polyamide layer; the polymer elastomer-modified polyamide layer is prepared by an interfacial polymerization reaction between an aqueous solution and an oil solution on the surface of a base film. The aqueous solution contains amine monomers, and the oil solution contains acyl chloride monomers and polymer elastomers.
2. The alkali-resistant nanofiltration membrane for separating cellulose-based substances and calcium and magnesium ions according to claim 1, characterized in that, The base film is prepared by phase inversion of polysulfone resin, polymer elastomer, polyethylene glycol and inorganic nanoparticles uniformly dispersed in a solvent.
3. The alkali-resistant nanofiltration membrane for separating cellulose-based substances and calcium and magnesium ions according to claim 2, characterized in that, The polysulfone resin is one of polysulfone and polyethersulfone; the polymer elastomer is at least one of poly(acrylonitrile-co-butadiene), polychloroprene, and polyvinylidene fluoride; the inorganic nanoparticles are at least one of lithium chloride nanoparticles, zirconium dioxide nanoparticles, and magnesium oxide nanoparticles; and the solvent is at least one of N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone.
4. The alkali-resistant nanofiltration membrane for separating cellulose-based substances and calcium and magnesium ions according to claim 1, characterized in that, The amine monomers include piperazine and second amine monomers, wherein the second amine monomer is at least one of m-phenylenediamine, diethylenetriamine, and triethylenetetramine; and the acyl chloride monomers are at least one of pyromellitic trimethylol chloride, terephthalic acid dimethylol chloride, and isophthalic acid dimethylol chloride.
5. A method for preparing an alkali-resistant nanofiltration membrane capable of separating cellulosic substances and calcium and magnesium ions as described in any one of claims 1 to 4, characterized in that, Includes the following steps: S1. Add polysulfone resin and polymer elastomer to a solvent. After the polysulfone resin and polymer elastomer have dissolved, add polyethylene glycol and inorganic nanoparticles to the system in sequence and stir continuously at room temperature for 12-24 hours. Then, reduce the stirring speed to degas the mixture and continue stirring for 12-24 hours to obtain a uniform casting solution. S2. The casting solution prepared in step S1 is coated and then immersed in water for phase inversion to obtain the base film; S3. The substrate membrane prepared in step S2 is immersed in an aqueous solution containing amine monomers. After immersion, the membrane is removed and excess solution on its surface is removed. Then, it is immersed in an oil solution containing acyl chloride monomers and polymer elastomers to carry out interfacial polymerization reaction and deposit a surface separation functional layer. Finally, the nanofiltration membrane with the surface separation functional layer is heat-treated to obtain the alkali-resistant nanofiltration membrane.
6. The method for preparing an alkali-resistant nanofiltration membrane capable of separating cellulose-based substances and calcium and magnesium ions according to claim 5, characterized in that, In step S1, the mass ratio of the polymer elastomer to the polysulfone resin is (0.1~0.3):1; the mass ratio of the solvent to the polysulfone resin is (3~6):1; the mass ratio of the polyethylene glycol to the polysulfone resin is (0.05~0.2):1; and the mass ratio of the inorganic nanoparticles to the polysulfone resin is (0.2~1):
1.
7. The method for preparing an alkali-resistant nanofiltration membrane capable of separating cellulose-based substances and calcium and magnesium ions according to claim 5, characterized in that, In step S2, the phase transformation temperature is 15~40℃ and the phase transformation time is 0.5~2.0min.
8. The method for preparing an alkali-resistant nanofiltration membrane capable of separating cellulose-based substances and calcium and magnesium ions according to claim 5, characterized in that, In step S3, the content of piperazine in the aqueous solution containing amine monomers is 0.02 g / mL, and the total content of the second amine monomers is 0.01~0.03 g / mL, based on the total volume of the aqueous solution; the soaking time is 1~5 min. In the oil phase solution containing acyl chloride monomer and polymer elastomer, based on the total volume of the oil phase solution, the content of acyl chloride monomer is 3.0 mg / mL, and the content of polymer elastomer is 0.5~2.0 mg / mL; the solvent of the oil phase solution is n-hexane and dichloromethane, and the volume ratio of n-hexane to dichloromethane is (35~45):1; the interfacial polymerization reaction time is 10~120 s.
9. The method for preparing an alkali-resistant nanofiltration membrane capable of separating cellulose-based substances and calcium and magnesium ions according to claim 5, characterized in that, In step S3, the heat treatment temperature is 50~80℃ and the time is 1~10min.
10. A method for preparing an alkali-resistant nanofiltration membrane capable of separating cellulose-based substances from calcium and magnesium ions according to any one of claims 5 to 9, characterized in that, The step also includes step S4, which involves immersing the alkali-resistant nanofiltration membrane prepared in step S3 in a mixed solution of deionized water and ethanol for preservation.